2023
DOI: 10.1101/2023.02.26.530135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acetylcholine engages distinct amygdala microcircuits to gate internal theta rhythm

Abstract: Acetylcholine (ACh) is released from basal forebrain cholinergic neurons in response to salient stimuli and engages brain states supporting attention and memory. These high ACh states are associated with theta oscillations, which synchronize neuronal ensembles. Theta oscillations in basolateral amygdala (BLA) underlie emotional memory, yet their mechanism remains unclear. Using brain slice electrophysiology in mice, we show large ACh stimuli evoke prolonged theta oscillations in BLA local field potential that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 87 publications
(153 reference statements)
0
6
0
Order By: Relevance
“…Unfortunately, there have been no anatomical investigations that have examined the expression of M3Rs in the BNC or studied cholinergic inputs to BNC CCK basket cells. However, electrophysiological studies have shown that BL CCK+ INs are activated by nicotinic receptors (Lee & Kim, 2019) and M3Rs (Bratsch‐Prince et al., 2023).…”
Section: Summary and Functional Considerationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Unfortunately, there have been no anatomical investigations that have examined the expression of M3Rs in the BNC or studied cholinergic inputs to BNC CCK basket cells. However, electrophysiological studies have shown that BL CCK+ INs are activated by nicotinic receptors (Lee & Kim, 2019) and M3Rs (Bratsch‐Prince et al., 2023).…”
Section: Summary and Functional Considerationsmentioning
confidence: 99%
“…There is evidence that CCK+ INs are activated by nicotinic receptors (Lee & Kim, 2019) and muscarinic type 3 receptors (M3Rs) (Bratsch‐Prince et al., 2023). Some SOM+ INs are hyperpolarized by release of ACh, whereas others are depolarized (Bratsch‐Prince et al., 2023).…”
Section: Cholinergic Basal Forebrain Projections To the Bncmentioning
confidence: 99%
See 3 more Smart Citations